Sport and exercise nutrition - Lanham-New, S. (Susan).; Nutrition Society (Great Britain). (Chichester, West Sussex, UK : Wiley-Blackwell, 2011)
'Now widely adopted on courses throughout the world, the prestigious Nutrition Society Textbook series provides students with the scientific basics in nutrition in the context of a systems and disease approach rather than on a nutrient by nutrient basis. In addition books provide a means to enable teachers and students to explore the core principles of nutrition and to apply these throughout their training to foster critical thinking at all times.This NS Textbook on Sport and Exercise Nutrition has been written to cover the latest information on the science and practice of sport and exercise nutrition. A key concept behind this textbook is that it aims to combine the viewpoints of world leading nutrition experts from both academia/research and a practical stand point. Plus where necessary there are additional practitioner based authors to ensure theory is translated into practice for each chapter in the form of either'practice tips' or'information sheets' at the end of relevant chapters.The textbook in essence can be divided into three distinct but integrated parts:Part 1: covers the key components of the science that supports the practice of sport and exercise nutrition including comprehensive reviews on: nutrients both in general and as exercise fuels; exercise physiology; hydration, micronutrients; and supplements. Part 2: moves into focusing on specific nutrition strategies to support different types of training including: resistance; power/sprint; middle distance/speed endurance; endurance; technical/skill, team; and specific competition nutrition needs.The unique format of this textbook is that it breaks down nutrition support into training specific as opposed to the traditional sport specific support. This reflects the majority of current sport and exercise requirements of the need to undertake concurrent training and therefore facilitating targeted nutrition support to the different training components through the various macro and micro training.
cycles.Part 3: explores some of the practical issues encountered in working in the sport and exercise nutrition field and includes key sport related topics such as: disability sport; weight management; eating disorders; bone and gut health; immunity; injury; travel; and special populations and situations.READERSHIP: Students of nutrition and dietetics at both undergraduate and postgraduate level. All those working in the field of nutrition and related health sciences'--Provided by publisher.
Nutrient basics / A. Collins, P. Hunking, and S. Stear -- Exercise physiology / S.M. Shirreffs -- Exercise biochemistry / S.D.R. Galloway -- Carbohydrate / A. Jeukendrup and C. Williams -- Protein and amino acids / P.W.R. Lemon -- Fat metabolism / B. Kiens and J.A. Hawley -- Fluids and electrolytes / S.M. Shirreffs -- Micronutrients / V. Deakin -- Supplements and ergogenic aids / H. Braun, K. Currell, and S. Stear -- Nutrition for weight and resistance training / S.M. Phillips and K. Baar -- Nutrition for power and sprint training / N.A. Burd and S.M. Phillips -- Nutrition for middle-distance and speed-endurance training / T. Stellingwerff -- Nutrition for endurance and ultra-endurance training / A. Bosch and K.M. Smit -- Nutrition for technical and skill-based training / S. Meltzer and N. Hopkins -- Nutrition for disability athletes / J. Crosland and E. Broad -- Competition nutrition / L.M. Burke -- Losing, gaining, and making weight for athletes / H. O'Connor and G. Slater -- Eating disorders and athletes / J. Sundgot-Borgen and I. Garthe -- Bone health / C. Sanborn, D.L. Nichols, and N.M. DiMarco -- Nutrition and the gastrointestinal tract for athletes / J. Pearce and J.O. Hunter -- Immunity / G. Davison and R.J. Simpson -- Travel / B. Lundy and E. Broad -- Population groups : I -- Population groups : II -- Training and competition environments / J.L. Fallowfield, J.D.J. Layden, and A.J. Allsopp.
Includes bibliographical references and index.
Keywords: Exercise -- Physiology; Sports -- Physiology; Nutritional Physiological Phenomena; Nutritional Sciences; Physical Fitness -- Physiology